2008
DOI: 10.1029/2007ja012632
|View full text |Cite
|
Sign up to set email alerts
|

Some ubiquitous features of the mesospheric Fe and Na layer borders from simultaneous and common‐volume Fe and Na lidar observations

Abstract: [1] High-accuracy atom density profiles, obtained by the simultaneous and commonvolume Fe and Na lidar measurements at Wuhan, China (30.5°N, 114.4°E), reveal some ubiquitous features of the Fe and Na layers on their borders. The Fe and Na lower boundaries show consistently a delicate stratification in which the lower boundary of the Fe layer is in general slightly higher than or coincident with that of the Na layer, with an overall mean altitude difference being about 0.2 km. Despite the existence of considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 38 publications
8
27
0
1
Order By: Relevance
“…They noticed that even though the individual density profiles appeared quite different, the temporal variations of Na and Fe layer parameters (abundances, centroid heights, and RMS widths) were highly correlated in most cases. The simultaneous and common-volume Na and Fe lidar observations at 30 • N revealed that Na and Fe lower boundaries always follow almost the same track and show consistently a delicate stratification with the Fe lower boundary being in general slightly higher than or coincident with that of the Na layer (Yi et al, 2007(Yi et al, , 2008. In addition, the Na layer always shows a few kilometers more extension on its top side than the Fe layer.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They noticed that even though the individual density profiles appeared quite different, the temporal variations of Na and Fe layer parameters (abundances, centroid heights, and RMS widths) were highly correlated in most cases. The simultaneous and common-volume Na and Fe lidar observations at 30 • N revealed that Na and Fe lower boundaries always follow almost the same track and show consistently a delicate stratification with the Fe lower boundary being in general slightly higher than or coincident with that of the Na layer (Yi et al, 2007(Yi et al, , 2008. In addition, the Na layer always shows a few kilometers more extension on its top side than the Fe layer.…”
Section: Introductionmentioning
confidence: 91%
“…The mean profiles will quantitatively show the relationship of the two background metal layers. In contrast to our previous work that only focuses on the relationship between the Na and Fe layer boundaries (defined by a given small density criterion) (Yi et al, 2008), here we will examine the relation between the Na and Fe density variations at all fixed altitudes over the main metal layer. An intriguing ubiquitous connection between the Na and Fe density variations at fixed altitudes on the layer bottom side is revealed for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…An example is shown in Figure 7a for 4 September 2012. Note that in the current study, the lower and upper boundaries of a metal layer are defined to be the altitudes where the densities are 2% of the nightly mean peak density, instead of a fixed density for two lidars as presented in Yi et al [2008]. For the total 704 pairs of Fe and Na density profiles over 12 nights, the Fe layer lower boundaries are plotted versus the Na lower boundaries in Figure 7b.…”
Section: Density Gradient In the Boundary Correlationmentioning
confidence: 99%
“…[27] A detailed study by Yi et al [2008] from 26 nights of observations at Wuhan (30.5°N, 114.4°E), China, has found a close correlation between Fe and Na boundary altitude variations, especially at the layer bottomside. Our Table Mountain observations reveal similar behavior, with higher correlations at the lower boundary (nearly 99%) and slightly lower correlation (~70%) at the upper boundary.…”
Section: Density Gradient In the Boundary Correlationmentioning
confidence: 99%
See 1 more Smart Citation